Water-soluble polyphenol synthesis via oxidative coupling polymerisation of β-arbutin with copper catalyst in alkaline media. (August 2016) - Hashimoto, Maria; Iwabuchi, Satoko; Oishi, Yoshiyuki; Shibasaki, Yuji
Graphical abstract: Highlights: Polymerisation of β-arbutin with Cu-catalyst in water via CC coupling was attained. The MW of the poly(β-arbutin) was as high as 7240. The partially octylated poly(β-arbutin) at OH position shows amphiphilic properties. The partially octylated polymer can encapsulate pyrene in water. Abstract: β-Arbutin (4′-hydroxyphenyl β-d -glucoside) was successfully polymerised in tris(hydroxymethyl)aminomethane hydrogen chloride (Tris-HCl, pH = 9.0) buffer solution with di-μ-hydroxo-bis[(N, N, N′, N′-tetramethylethylenediamine)copper(II)] chloride as the catalyst in the presence of dioxygen. The polymer was obtained in good yield (up to 99%), with a number-average molecular weight up to 7200 and a molar-mass dispersity of 1.5 estimated by GPC; the 5- and 10-wt% loss temperatures for this polymer under nitrogen were 255 and 270 °C, respectively. The polymer structure was characterised by FTIR, 1 H NMR, and 13 C NMR spectroscopy, from which the structure of the polymer was determined to be poly(β-d -glucoside-4′-hydroxy-3, 5-phenylene) (poly(βArb)), whose OH functional groups were almost preserved (>95%) throughout the polymerisation. The octylation of the OH functional groups of the poly(βArb) backbone was conducted with octyl bromide in the presence of potassium carbonate in N, N-dimethylformamide (DMF) to give the partially octylated polymer, which was soluble in both D2 O and DMSO- d 6 NMR solvents. Despite the good solubility of the polymer in these solvents, broadening of the signals corresponding to the octyl moiety was observed in the spectrum of the polymer dissolved in D2 O, suggesting that the polymer could form micelles in a selective solvent. A homogeneous fluorescence was observed in water when pyrene with the polymer solution in DMF was diluted with an excess of deionised water, indicating the successful encapsulation of the pyrene chromophore in the micelle core.